Implementasi Algoritma Topsis pada Decision Support System Pemilihan Perguruan Tinggi Swasta Program Studi Informatika/Teknik Informatika - Widodo, Sri; Gutama, Deden Hardan; Wijaya, Dhina Puspasari; Prastowo, Wahit Desta (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PDDIKTI noted that the number of new students in Indonesia has continued to increase since the academic year 2016/2017. The increase in the number of new students every year proves that the level of public awareness of the importance of education is increasing. On this basis, the author initiated the design of a system that could be used by prospective new students or students who have completed in Higher Secondary School educators and their equivalents. The system the author designed is a Decision Support System by implementing topsis algorithms on its calculations. The result of this research is a system of decision support for the selection of PTS specialized program of study in Informatics/Technology.